The Application of Islamic Value-Based Empowerment of MSMEs to Improve the Performance of Micro Businesses in Panongan Subdistrict, Tangerang - Nur Jamaludin; Muizzudin Muizzudin (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
The rapid population growth in Panongan, a subdistrict within Tangerang Regency, has surpassed regional averages, with rates of 6.5%, 3.4%, and 2.7% for Panongan, Tangerang Regency, and Banten Province respectively. This demographic surge presents challenges in terms of economic, social, and population-related issues while also offering avenues for market expansion and novel economic prospects. This study aimed to elucidate the application of Islamic value-based empowerment for Micro, Small, and Medium Enterprises (MSMEs) through the community engagement program executed by the Faculty of Economics and Business Islam at the University of Cendekia Abditama Tangerang. The program was designed to assist 20 MSMEs in Panongan Subdistrict. Employing Participatory Action Research (PAR), which emphasizes collaboration between researchers and the targeted MSME communities, this study investigated the effects of Islamic value-based empowerment on business aspects. The findings revealedthat this approach enhances Islamic value-based empowerment on the economic aspect, business ethics aspect, marketing aspect, packaging design, bookkeeping, legal aspects, and fiqh muamalah aspect among MSMEs. This empowerment has consequently created extensive prospects for business expansion, contributing to increased prosperity.